Tomography Imaging of Lithium Electrodeposits Using Neutron, Synchrotron X-Ray, and Laboratory X-Ray Sources: A Comparison - Magnier, Lucile; Lecarme, Lauréline; Alloin, Fannie; Maire, Eric; King, Andrew; Bouchet, Renaud; Tengattini, Alessandro; Devaux, Didier (Frontiers in Energy Research, 2021)
X-ray and neutron imaging are widely employed for battery materials, thanks to the possibility to perform noninvasive in situ and in operando analyses. X-ray tomography can be performed either in synchrotron or in laboratory facilities and is particularly well-suited to analyze bulk materials and electrode/electrolyte interfaces. Several post-lithium-ion (Li-ion) devices, such as Li–sulfur, Li–O2, or all-solid-state Li batteries, have an anode made of metallic Li in common. The main failure mode of Li batteries is the inhomogeneity of the Li electrodeposits onto the Li anode during charge steps, leading to dendrite growth and low Coulombic efficiency. X-ray tomography is a powerful tool for studying dendrites as it provides useful information about their locations, dynamics, and microstructures. So far, the use of neutron tomography is scarcely reported for Li deposit analysis due to the difficulty in reaching sufficient image resolution to capture the deposit microstructure, that is, typically below 10–20 µm. The very different interactions of X-rays and neutrons with Li, which has significantly different opacity in the two cases, make the two techniques highly complementary. Notably, the capacity of neutrons to discern different Li isotopes is pivotal to getting an insight into the composition of Li deposits by distinguishing between Li originating from an electrode (6Li in this study) and Li originating from the Li salt electrolyte (mainly in 7Li here). Indeed, the theoretical linear neutron attenuation coefficient of 6Li is about 15 and 2,000 times larger than that of natural Li and 7Li, respectively. Therefore, a high imaging contrast difference is obtained between 6Li (high attenuation) and natural Li and 7Li (lower attenuations), which could allow a better understanding of the origin of the Li comprising the electrodeposits. In this work, we report, as a proof of concept, an in situ neutron tomography imaging of Li electrodeposits in a cycled Li symmetric cell. The electrochemical cell comprises a natural Li electrode, a 6Li electrode, and a deuterated liquid electrolyte. The neutron tomographies are compared with X-ray tomography images of the same electrochemical cell acquired both at an X-ray synchrotron beamline and at a laboratory X-ray tomograph. Neutron tomography is shown to be compatible with in situ analysis and capable of capturing the overall morphology of the Li deposits in good accordance with X-ray tomography analyses.